Needs of the caregivers of people requiring palliative care in an urban area of Pondicherry, South India - Daya A., Praveena; Sarkar, Sonali; Kar, Sitanshu Sekhar (International Journal Of Community Medicine And Public Health, 2018)
Background: There is an increasing need to provide palliative care services globally. All these chronic, life limiting diseases not only affect the patients but also affect their caregivers in various aspects. The aim of the study was to assess the needs of caregivers of people requiring palliative care in an urban area of Pondicherry, South India. Methods: An exploratory descriptive study was conducted in 1004 households with 3554 individuals in two selected areas under an urban PHC in Pondicherry. Needs of the 21 caregivers who provided care for 22 patients were studied using Needs Assessment Tool: Progressive Disease (NAT: PD). Data was analysed using IBM SPSS Software version 20. Levels of concern for various domains were rated subjectively as none, some, significant and expressed in proportions. Content analysis was done for the qualitative data after translation and transcription. Results: Caregivers faced physical, psychological, financial, social and spiritual issues related to care-giving. Physical issues reported were sleeplessness, fatigue and back pain. Common psychological issues reported were depression, hopelessness and getting tensed frequently. Financial issues of caregivers were related to loss of income and loss of family savings for the treatment charges of patients. Social issues observed were avoiding going out or attending festivals, lack of social support and lack of time to spend enough time with their spouse and children. Conclusions: Caregivers are exposed to a long-term stress starting from the diagnosis of the patient’s illness continuing even after the death of patient. So in this way the caregivers are exposed to higher level of stress than the patients, which needs to be addressed appropriately.